Predator perception of aposematic and cryptic color morphs in two Oophaga species - Vasiliki Mantzana‐Oikonomaki; Ariel Rodríguez; Giselle Castillo‐Tamayo; Roberto Ibáñez; Heike Pröhl (Ecology and Evolution)
Abstract Animals that are toxic often advertise their unprofitability to potential predators through bright aposematic colors while cryptic ones blend in with their natural background to avoid predators. In the poison dart frogs, Oophaga pumilio and O. granulifera, some populations in Costa Rica and Panama display cryptic green and aposematic red color morphs. We herein used reflectance spectra from the dorsum of red and green morphs of these frogs to estimate their perception by the visual systems of three potential predators (birds, lizards, and crabs) against three natural backgrounds (leaves, trunks and leaf litter). Statistical analyses revealed no strong differences in color contrast against backgrounds between the two frog species. However, strong effects of frog morph, predator, background, and their interactions were observed. When viewed against diverse backgrounds, red frogs of both Oophaga species are more color conspicuous to birds and Anoline lizards than to crabs. A strong effect of species was observed on luminance contrast. Concerning the latter, green frogs particularly in O. granulifera appear more conspicuous than red frogs, while birds perceive higher brightness contrasts than lizards or crabs. Our results further support the importance of birds and lizards as Oophaga predators and provide a first quantitative comparison of conspicuousness between these two frog species.